2016
DOI: 10.1001/journalofethics.2016.18.9.nlit1-1609
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional Clinical Ethics Education: The Promise of Cross-Disciplinary Problem-Based Learning

Abstract: A review of Lin et al.'s pilot study exploring the effects of an interprofessional, problem-based learning clinical ethics curriculum on Taiwanese medical and nursing students' attitudes towards interprofessional collaboration highlights the benefits of interprofessional collaboration and offers insight into how problembased learning might be universally applied in ethics education. Interprofessional collaboration is an ideal approach for exploring ethical dilemmas because it involves all relevant professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 13 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…From a public health viewpoint, it is also clear that health professions should seek to promote health equity at the community level (Browne et al, 2012 ). Therefore, educational interventions that allow individuals to reflect on dilemma situations and share their opinions with colleagues, such as problem-based learning classes using various real cases, will be required, which can improve their coping strategies for the situation and professional development (Khatiban et al, 2019 ; Kurtz & Starbird, 2016 ; Ribeiro et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…From a public health viewpoint, it is also clear that health professions should seek to promote health equity at the community level (Browne et al, 2012 ). Therefore, educational interventions that allow individuals to reflect on dilemma situations and share their opinions with colleagues, such as problem-based learning classes using various real cases, will be required, which can improve their coping strategies for the situation and professional development (Khatiban et al, 2019 ; Kurtz & Starbird, 2016 ; Ribeiro et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Problem-based learning, which typically uses specific case scenarios to teach basic and clinical medicine through self-directed and cooperative learning, has been proposed as an effective way of providing ethics education for healthcare students [ 49 ]. Similarly, it has been found that working with critical incidents could be an effective way of dealing with the real-life ethical dilemmas [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interprofessional preparation of case material ensures that adequate details are included to allow students to apply their profession-specific knowledge and skills to address the interface between clinical and ethical considerations, resulting in a more authentic learning experience for all students. 20…”
Section: Discussionmentioning
confidence: 99%